2019
DOI: 10.1111/tpj.14595
|View full text |Cite
|
Sign up to set email alerts
|

Linking water relations and hydraulics with photosynthesis

Abstract: Summary For land plants, water is the principal governor of growth. Photosynthetic performance is highly dependent on the stable and suitable water status of leaves, which is balanced by the water transport capacity, the water loss rate as well as the water capacitance of the plant. This review discusses the links between leaf water status and photosynthesis, specifically focussing on the coordination of CO2 and water transport within leaves, and the potential role of leaf capacitance and elasticity on CO2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 146 publications
(312 reference statements)
9
91
0
Order By: Relevance
“…If there exists an adaptive trade-off relation between hydraulic efficiency and cavitation resistance among Pinaceae species ( Choat et al , 2011 ; Gleason et al , 2016 ; Maherali et al , 2004 ), it means photosynthesis could have a negative association with cavitation resistance among the non-threatened species globally. As expected by either the carbon economy theory ( Augusto et al ., 2014 ) or k l – P n coordination ( Brodribb et al , 2002 ; Scoffoni et al , 2016 ; Xiong et al , 2019 ), the PGLS output of the 13 species did support the P 50 – P n trade-off ( Fig. 5A , P = 0.02), which was consistent with some other studies on gymnosperm species ( Maherali et al , 2006 ; Pittermann et al ., 2012 ; Sterck et al ., 2012 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If there exists an adaptive trade-off relation between hydraulic efficiency and cavitation resistance among Pinaceae species ( Choat et al , 2011 ; Gleason et al , 2016 ; Maherali et al , 2004 ), it means photosynthesis could have a negative association with cavitation resistance among the non-threatened species globally. As expected by either the carbon economy theory ( Augusto et al ., 2014 ) or k l – P n coordination ( Brodribb et al , 2002 ; Scoffoni et al , 2016 ; Xiong et al , 2019 ), the PGLS output of the 13 species did support the P 50 – P n trade-off ( Fig. 5A , P = 0.02), which was consistent with some other studies on gymnosperm species ( Maherali et al , 2006 ; Pittermann et al ., 2012 ; Sterck et al ., 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that the hydraulic efficiency of branch has a tight association with leaf photosynthetic capacity ( Brodribb et al , 2002 ; Scoffoni et al , 2016 ; Xiong et al , 2019 ). If there exists an adaptive trade-off relation between hydraulic efficiency and cavitation resistance among Pinaceae species ( Choat et al , 2011 ; Gleason et al , 2016 ; Maherali et al , 2004 ), it means photosynthesis could have a negative association with cavitation resistance among the non-threatened species globally.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that non-vascular plants have not improved g m and thus photosynthesis, because to do so it would be necessary to implement other aspects such as for vascular systems, plant height, and stomatal regulation. Indeed there is evidenceat least from pteridophytes to angiospermsof positive scaling among A area , g m , leaf venation and hydraulic conductivity (Brodribb et al, 2007;Flexas et al, 2013b;Scoffoni et al, 2016;Xiong et al, 2017;Xiong and Nadal, 2019). Additionally, mosses of the genus Polytrichum, which have at least partially functional hydroids (i.e.…”
Section: Key Role Of Mesophyll Conductance and Other Physiological Trmentioning
confidence: 99%
“…Maximum g s is therefore constrained by the plant’s hydraulic conductance, which is mainly related to leaf hydraulic conductance ( K leaf ) in most plants (Sack & Holbrook, 2006). Indeed, a tight correlation between K leaf and photosynthesis has been widely observed (Brodribb et al ., 2005, 2007; Nardini et al ., 2014; Xiong et al ., 2015b; Scoffoni et al ., 2016; Xiong & Nadal, 2020). K leaf is largely determined by leaf vein density because an increased amount of veins brings xylem tissues specialized for water transport closer to the evaporation sites inside the leaf (Brodribb et al ., 2007; Buckley et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%